Quasilinear observables in dark energy cosmologies - Rampf, Cornelius; Villa, Eleonora; Amendola, Luca (Arxiv, 2017)
What are the fundamental limitations of reconstructing the properties of dark energy, given cosmological observations in the quasilinear regime in a range of redshifts, to be as precise as required? The aim of this paper is to address this question by constructing model-independent observables, whilst completely ignoring practical problems of real-world observations. Non-Gaussianities already present in the initial conditions are not directly accessible from observations, because of a perfect degeneracy with the non-Gaussianities arising from the nonlinear matter evolution in generalized dark energy models. By imposing a specific set of evolution equations that should cover a range of dark energy cosmologies, we however find a constraint equation for the linear structure growth rate